Effect of Internal Reflectors on Daily Performance of Double Slope Solar Stills with Porous Fin Absorber Plate - Nova Risdiyanto Ismail; Purbo Suwandono; Dadang Hermawan; Akhmad Farid; Frida Dwi Anggraeni (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2024)
The potential of energy and sea water in Indonesia is relatively high, but it has not been utilized massively to reduce the shortage of fresh water on the islands. Utilization of this potential can use solar stills. Solar still is a relatively cheap technology, easy to obtain materials, environmentally friendly and easy to construct, but this technology has shortcomings in its low productivity. Efforts to increase productivity have been made by many researchers, but there has not been a study of internal reflector integration in a double slope solar still using a porous absorbent plate tested for 23 hours. This study aims to examine the effect of adding an internal reflector on the performance of a double slope solar still. The performance of the double slope solar still is identified by evaluating freshwater productivity and efficiency. This research was conducted experimentally comparing with and without internal reflector. The addition of internal reflectors varies in placement, as for the placement on the north and south sides (RUS), the south side (RS), and the north side (RU). Data collection starts at 07.00 p.m. until 06.00 a.m the next day and is carried out for 5 days. Research comparing the performance of RUS, RS, RU compared to TR and concluded that there is an increase in temperature of fins, seawater and cover glass when using the addition of internal reflector. The increase in temperature has an effect on daily productivity for RUS, RS and RU between 12.88-16.13%, 8.71-12.56%, and 1.70-2.88%, respectively. In addition, the addition of the internal reflector has a positive effect on increasing the daily efficiency for RUS, RS and RU between 12.69-15.93%, 8.60-12.46% and 1.65-2.82%, respectively.